Implementasi Kebijakan Penyusunan Laporan Penyelenggaraan Pemerintah Daerah Tahun 2020 di Pemerintah Kota Pangkalpinang - Irma Mutiahsari; Azhar Azhar; M. Husni Thamrin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The objective of this research is to find out how the implementation of the Minister of Home Affairs Regulation Number 18 of 2020 concerning the Implementation Regulation of Government Regulation Number 13 of 2019 concerning Reports and Evaluation of the Implementation of Local Government carried out by Pangkalpinang City Government in 2020, the supporting and hindering factors in the implementation. The research focused on preparing reports based on government policies using the implementation theory of George Edwards III. Data collecting through document analysis, interviews, and observations using a qualitative approach. Based on the findings in the field, the implementation of Policy for Preparing Regional Government Implementation Reports for 2020 in Pangkalpinang City Government has not gone well. Inhibiting factors include a not yet optimal communication between the central government and local governments in delivering policy information, inadequate quantity of human resources to prepare various kinds of reports, uneven supporting facilities for the preparation of LPPD in each regional agency , a not yet optimal commitment of several regional agencies to meeting data  and documents needed to improve the quality of Key Performance Indicators (IKK), the lack of  coordination among regional agencies in data fulfillment, and the unavailability of a Standard Operational Procedure (SOP). Supporting factors include good communication between the Secretariat Team and drafting officers, the quality of human resources in terms of education, high commitment of the Secretariat Team, which is chaired by the Regional Secretary, and drafting officers.